If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2z + -5) = 7(z + -1) Reorder the terms: 3(-5 + 2z) = 7(z + -1) (-5 * 3 + 2z * 3) = 7(z + -1) (-15 + 6z) = 7(z + -1) Reorder the terms: -15 + 6z = 7(-1 + z) -15 + 6z = (-1 * 7 + z * 7) -15 + 6z = (-7 + 7z) Solving -15 + 6z = -7 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. -15 + 6z + -7z = -7 + 7z + -7z Combine like terms: 6z + -7z = -1z -15 + -1z = -7 + 7z + -7z Combine like terms: 7z + -7z = 0 -15 + -1z = -7 + 0 -15 + -1z = -7 Add '15' to each side of the equation. -15 + 15 + -1z = -7 + 15 Combine like terms: -15 + 15 = 0 0 + -1z = -7 + 15 -1z = -7 + 15 Combine like terms: -7 + 15 = 8 -1z = 8 Divide each side by '-1'. z = -8 Simplifying z = -8
| 2x+32=0-8 | | -11x-7=-12x-5 | | 25x-17=o | | 16x=83 | | -13n=247 | | 0.15(x+40)=0.05 | | -87.5=2.6n+5.4(1+6.4n) | | 5m+4-9m=32 | | 2(2+4m)-9=45 | | 400=2X*40 | | 2(-2r+4)=-2(r+5) | | 2(y)+25+2y-30=180 | | 3b+2(7b+b)-3= | | M+8=-8 | | 0.15(x+40)= | | 2x-7y-14=0 | | 3b+4b-3=11 | | 15x-25(5-x)=275 | | -20n=-120 | | 2lx-5l=22 | | 3-z=4a+12 | | -20=-120 | | 14x-2y=22 | | 10=20+2(3x) | | 14=k/5 | | 7(6(4x-1)-2x+12)= | | 10-2(3x+4)=21+6x | | 2a+20=48 | | x-15=0.40x | | 6x^3+96x=0 | | 5n+34=2(1+7n) | | 9x^2+12x+8=8 |